A Method for Calculating the Bearing Capacity of Basic Members of an Underground Concrete-Filled Steel Tube Supporting Arch with a D-Shaped Cross Section - Weiteng Li; Zijian Wang; Zhaoshun Jing; Yuanzhen Li; Yuchun Mei; Chunqing Liu (Buildings)
High-strength concrete-filled steel tube (CFST) arches have been widely applied in underground engineering, among which there are special-shaped arches such as D-shaped sections. At present, most studies have concentrated on members with square or circular sections, while relatively few studies have been conducted on D-shaped section members. In this study, firstly, D-shaped sections were initially transformed into sections with a part square and part elliptical shape using an equivalent section method. The formulas for the axial compression and pure bending bearing capacities of the basic D-shaped CFST members were deduced using unified theory, and the bearing capacity of the D-shaped members was calculated in a given case. Secondly, numerical simulations of axial compression and pure bending of the basic CFST members with three section types (square, circular, and D-shaped) were carried out using ABAQUS software. To ensure the reliability of the numerical simulations, the concrete damage constitutive model and the elastic–plastic model were adopted to simulate the core concrete and the steel tube, respectively. In the results, the axial compression and pure bending bearing capacities of the D-shaped section obtained via theoretical calculation were 2339.6 kN and 84.8 kN·m, respectively, while the results obtained via numerical simulation were 2335.8 kN and 85.4 kN·m, respectively, which were relatively close. Among the three section types of members, the D-shaped members had the highest axial compression bearing capacity, which was 1.45% and 4.58% higher than those of the circular and square section members, respectively. However, their bending moment bearing capacity was relatively low. The stress distribution of the D-shaped members presented a characteristic where the circular part dominated, and the stress transfer effect of the members was favorable. In practical engineering, when the surrounding rock pressure is high and evenly distributed, D-shaped section arches can be selected, and increasing the proportion of the square area in D-shaped sections can enhance the overall flexural capacity of arches.